Advancing Responsible AI Governance through Decentralized Policy Enforcement Frameworks for Ethical Autonomous Agent Behavior - Derek Ellsworth (Computational Intelligence Systems, 2026)
The rapid proliferation of autonomous agents across critical socio-technical infrastructures has necessitated a paradigm shift from centralized regulatory oversight toward dynamic, decentralized governance models. As artificial intelligence systems transition from passive tools to proactive decision-making entities, the challenge of ensuring ethical alignment becomes increasingly complex. This research paper explores the conceptualization and implementation of decentralized policy enforcement frameworks designed to govern autonomous agent behavior in real-time. By leveraging distributed ledger technologies, consensus protocols, and modular policy engines, the proposed framework facilitates the local enforcement of global ethical standards without relying on a single point of failure or a central regulatory authority. The discussion delves into the structural trade-offs between system performance and governance granularity, emphasizing the need for robust infrastructures that can withstand adversarial manipulation while maintaining fairness and transparency. Through a comprehensive analysis of system-level architectures, the paper argues that decentralized enforcement provides a more resilient path for responsible AI governance by embedding policy directly into the operational fabric of agent environments. The findings suggest that such frameworks not only enhance accountability but also foster institutional trust by providing verifiable audit trails of agent compliance. This study concludes with a forward-looking perspective on the sustainability of decentralized governance and its implications for the future of human-AI collaboration in high-stakes domains such as finance, healthcare, and urban management.